Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.14712/23366052.2016.11
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors influencing outcomes of a five-week youth expedition in the Himalayas using the sail training programme self-assessment toolkit

Abstract: Much evidence to link youth expeditions and gap years with a range of outcome benefits for participants exists, but to date, there have been relatively few insights into what exactly brings about these reported outcomes. A modified version of the Sail Training Voyage Toolkit (2011) was used to evaluate outcomes of a five-week British Exploring Society youth expedition in the Himalayas. Data generated from 22 participants completing the modified Sail Training Voyage Feedback Form at the end of their expedition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Youth expeditions are often regarded as beneficial and even “life-changing” experiences for young people (Allison et al, 2018; Kellert & Derr, 1998; Stott et al, 2016), however the evidence on their perceived long-term impact is limited (Takano, 2010). Youth expedition organizations, such as the British Exploring Society, have a genuine need to conduct research, in order to learn if these experiences influence participants’ lives, and if so, what are these influences, which in turn can inform future practices.…”
mentioning
confidence: 99%
“…Youth expeditions are often regarded as beneficial and even “life-changing” experiences for young people (Allison et al, 2018; Kellert & Derr, 1998; Stott et al, 2016), however the evidence on their perceived long-term impact is limited (Takano, 2010). Youth expedition organizations, such as the British Exploring Society, have a genuine need to conduct research, in order to learn if these experiences influence participants’ lives, and if so, what are these influences, which in turn can inform future practices.…”
mentioning
confidence: 99%
“…These skills and attributes are understood to be developed through an increased ability to effectively manage our emotions, thoughts and behaviours -particularly through challenging circumstances (Allison & Von Wald, 2012;Department for Education, 2015;Public Health England, 2015;Stott, Allison, Von Wald, & Fakunle, 2016). A useful systematic review of research on youth expeditions was undertaken by Stott et al (2015) which confirms the need for research using larger samples than the proliferation of anecdotal studies.…”
Section: Emerging Gaps In Existing Knowledgementioning
confidence: 96%
“…This can be achieved through OAA provision, when delivered in a way that successfully provides an immersive experience, meets the bespoke needs of participants and is evidenced in an appropriate form [8]. Several studies have shown that conditions experienced on an expedition can result in improved psychological well-being [9][10][11][12]. However, few studies have examined the impact of expeditions for people adjusting to life-changing circumstances, such as sustaining career-ending physical injuries or the diagnosis of a trauma-related mental health disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have reported on how short-term expeditions influence well-being benefits and these are limited by focusing on the immediate expedition, meaning that longerterm impacts are unclear [9][10][11][12]. Further, only one study has addressed the unique context of expeditions involving military veterans [13].…”
Section: Introductionmentioning
confidence: 99%